2018
DOI: 10.3126/jpan.v7i2.24608
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and Endocrine system: A narrative review

Abstract: Cannabis is one of the most abused substances worldwide. The active component of cannabis is THC which has multiple effects in the endocrine system in both animal models and humans. The interest of scientific community in endocrine effects of cannabis is recent. We present a narrative review of endocrine effects of cannabis in different organ system along with description of possible mechanism both in the animal models and as well as in humans. We also highlight the need of research in this area especially in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Cannabis use can lead to subtle lowering of T4 hormone, decrease in testosterone, oligospermia and impotency in male, and inhibit the secre on of growth hormone especially impac ng the fetal growth. Overall cannabis has a depressant effect on most of the hormones but their clinical [27][28] implica ons are yet to be revealed clearly. The impact of use of substances like cocaine and inhalants on endocrine system are less studied.…”
Section: Substance Use As Risk Factor For Endocrine Disordermentioning
confidence: 99%
“…Cannabis use can lead to subtle lowering of T4 hormone, decrease in testosterone, oligospermia and impotency in male, and inhibit the secre on of growth hormone especially impac ng the fetal growth. Overall cannabis has a depressant effect on most of the hormones but their clinical [27][28] implica ons are yet to be revealed clearly. The impact of use of substances like cocaine and inhalants on endocrine system are less studied.…”
Section: Substance Use As Risk Factor For Endocrine Disordermentioning
confidence: 99%
“…In another study, it was found that THC leads to a 65% reduction in testosterone levels, which lasted for an hour. Therefore, it was concluded that the consequences of chronic exposure are less severe compared to acute administration and can be related to the development of resistance against other drugs ( Bovolin et al, 2017 , Sharma and Balhara, 2018 ). In experiments conducted on different animals for the study, the effect of acute dose of cannabinoids showed an increase in ACTH and GC levels with respect to the dose of cannabinoids and showed a similar effect as perceived by the increase in the CRH level ( Franks et al, 2020 ).…”
Section: Marijuana and Health Effects: Conflicting But Interesting Outcomesmentioning
confidence: 99%
“…Plasma cortisol levels are increased by intravenous treatment with delta-9-THC in a dose-dependent manner in both controls and Cannabis -dependent individuals. However, a blunted response was observed in frequent Cannabis users compared to healthy controls ( Sharma and Balhara, 2018 ). Ovulation is allowed through the presence of high intrafollicular levels of endocannabinoids, i.e.…”
Section: Marijuana and Health Effects: Conflicting But Interesting Outcomesmentioning
confidence: 99%